Mexican Gothic - Moreno-Garcia, Silvia (New York : Del Rey, 2020)
"The acclaimed author of Gods of Jade and Shadow returns with a darkly enchanting reimagining of Gothic fantasy, in which a spirited young woman discovers the haunting secrets of a beautiful old mansion in 1950s Mexico"--
Keywords: Haunted houses -- Fiction. -- Mexico; Investigations -- Fiction; Debutantes -- Fiction; Cousins -- Fiction; Country homes -- Fiction. -- Mexico; Gothic fiction; Gothic fiction